Academic citizenship through the bundle of academic roles - Fremstad, Ester; Ewins, Kristin (Journal of Praxis in Higher Education, 2024)
As academic developers and higher education researchers, we, the authors, have pondered why engaging in public discourse is often found to be difficult by academics and how we can conceptualise and help prepare for the role of academic citizen in general and in more discipline-specific terms. Rather than approaching citizenship as an extraordinary task or role for the academic, we find that it may be best understood and approached as integral to being a researcher and teacher. We use perspectives on the knowledge society and the concept of co-production of science and society to suggest some conceptual inroads for understanding what shape the task of academic citizenship might take.